The Values of Faith-Based Moral Education in the Perspective of Sheikh Nawawi al-Bantani (Analytical Study of the Book of Qami’u at-Tughyan) - Cahyawati, Hermi (Proceeding International Conference on Religion, Science and Education, 2022)
The national education paradigm is now required to return to its original home which is rich in moral values, so the orientation of national education has been changed towards the formation of principles and reviving moral awareness, not only focusing on cognitive development as previously held. Because moral awareness is able to encourage someone to carry out the duties and obligations that are ordered as well as possible. Although it feels very heavy and often requires sacrifices, such as the sacrifice of interests, energy, costs, time, and feelings, it is joyful and happy. Modern education in Indonesia was introduced by foreign nations, especially the dutch. In the early 20th century, the dutch colonial government implemented ethical policies, one of which was education. They provide opportunities for indigenous people to get an education. However, those who could enjoy education at that time were the upper middle class (aristocrats). Also the aim is to produce educated people who can later work in the government bureaucracy and plantations with low wages. The dutch colonials in the past built schools only to find educated employees with low wages. As a large and fertile nation, Indonesia must of course abandon this kind of education model. As a consequence, if left unchecked, it will only create two different types of generations, one who is good at world affairs but doesn’t know religion, and the other is smart in religion but stupid in world affairs. Moral education is a conversation that will never run out, especially in Indonesian society that still strongly upholds moral values that come from religious teachings. In its history, Indonesia has quite a number of influential figures both locally and internationally, including in the religious field. The figure of Sheikh Nawawi Al-Bantani became a reference for the nation’s teachers in exploring sources of religious scholarship. So in this article, we will look for various values that are closely related to faith-based moral education from his perspective. At the same time, its relevance to moral education will be sought in modern times. The values of faith-based moral education in the book Qami’u at-Tughyan by Sheikh Muhammad Nawawi al-Bantani can be categorized into five main things, namely: (1) moral values to Allah; (2) moral values to the Prophet Muhammad; (3) moral values to scholars; (4) moral values to fellow human beings; (5) moral values towards oneself. Of course, these values are still very relevant throughout the ages as long as human civilization still exists. Regardless of the religion of any human in this world, but kindness to fellow humans is a manifestation of the sweet fruit of a religious person.